UTILIZATION OF WAROPEN FOLKLORE AS CHARACTER EDUCATION DEVELOPMENT FOR THE WAROPEN COMMUNITY IN YAPEN WAROPEN REGENCY - Iwong, Henry Christope (NOKEN : Jurnal Pengelolaan Pendidikan, 2024)
Abstract Waropen folklore is an inseparable part of the culture of the Waropen people in Yapen Waropen Regency, Papua. This study aims to examine the character education values contained in Waropen folklore and their relevance in shaping the character of the community. A qualitative approach with ethnographic methods was used to analyze thirteen titles of Waropen folklore. The results showed that Waropen folklore contains various character education values, including love and affection, caring and empathy, cooperation, courage, fortitude and commitment, fairness, helpfulness, humor, independence and self-confidence, loyalty, patience, pride, resourcefulness, and responsibility. These values are internalized by the Waropen community through storytelling and the exemplary figures in the stories. This study shows that Waropen folklore has great potential in developing community character education, especially in instilling moral and ethical values.